Breeding season diet of Scarlet Ibises and Little Blue Herons in a Brazilian mangrove swamp - Olmos, Fábio [UNESP]; Silva E Silva, Robson; Prado, Ariadne (Waterbird Soc, 2001)
We studied the diet composition and overlap of Scarlet Ibises (Eudocimus ruber) and Little Blue Herons (Egretta caerulea in a mangrove swamp in southeast Brazil during the 1996-1997 breeding season, which occurs during the rainiest period. Crabs comprised 95% of all prey taken by the ibises and 80% of the prey of the herons, Nevertheless, diet overlap was small (similar to 30%) due to ibises feeding mostly on Uca spp. and Eurythium limosum crabs, which were taken from their burrows; the herons fed on the arboreal and semi-arboreal Aratus Pisonii and Metasesarma rubripes crabs. Divergent hunting strategies of ibises (tactile foragers) and herons visually-oriented predators) explains the diet segregation when preying on an ecologically diverse crab guild, but it is unclear why herons prey rarely on fiddler crabs. Scarlet Ibises bred successfully while feeding oil estuarine organisms living in low salinities in the mangroves, showing that mangroves may be adequate foraging habitats for chick-rearing ibises during periods of low salinity.
Keywords: Carcinophagy; Crabs; Diet; Ecological separation; Egretta caerulea; Eudocimus ruber; Little blue heron; Mangrove; Niche; Scarlet Ibis; Segregation; South America; Breeding season; Diet; Foraging behavior; Mangrove; Niche partitioning; Wader; Brazil; Aratus pisonii; Decapoda; Eurythium limosum; Metasesarma rubripes; Uca